Visible light induced Knoevenagel condensation: A clean and efficient protocol using aqueous fruit extract of tamarindus indica as catalyst - Pal, Rammohan (International Journal of Advanced Chemistry, 2014)
Visible light induced a highly efficient and environmentally-friendly Knoevenagel condensation of various aliphatic and aromatic aldehydes with malononitrile has been achieved in excellent yield in presence of aqueous tamarind juice. The tamarind juice could be simply prepared from unripe fruit of Tamarindus indica in water and the reactions go to completion within 2-7 min. A plausible mechanism of light induced Knoevenagel condensation reaction catalyzed by tamarind juice was discussed.   Keywords: Knoevenagel condensation, visible light, aqueous tamarind juice, aldehydes, malononitrile.